Creativity of the Student Anti-Corruption Movement (Instilling 9 Anti-Corruption Values from an Early Age with Dokoro Elementary School Students) (Journal of Creativity Student, 2022)
Anti-corruption education is very important given the increasing number of corruption cases every year. Moreover, the largest number of corruption is in the vortex of government institutions which incidentally are people who have a qualified educational background. Seeing this reality, academics have to start racking their brains to tackle corruption cases from the roots. Thus, this article was compiled using a literature review that refers to the latest articles and journals. This paper is also prepared based on a case study in one of the group assignments, so that it is expected to be able to provide a comprehensive explanation of the importance of Anti-Corruption Education.